Mark Twain in Japan the cultural reception of an American icon - Ishihara, Tsuyoshi, 1971-; ebrary, Inc. (Columbia : University of Missouri Press, 2005)
"Explores the history of Mark Twain's reception in Japan in the spheres of books, children's magazines, and anime, the impact of Japanese translations on Twain's public image, how Japanese culture has transformed Japanese versions of Twain's works, and how Japan is culturally influenced by America and America by Japan"--Provided by publisher.
Includes bibliographical references and index.
Electronic reproduction.
Keywords: Twain, Mark, -- 1835-1910 -- Appreciation -- Japan; Twain, Mark, -- 1835-1910 -- Translations into Japanese -- History and criticism; American literature -- Appreciation -- Japan; Books and reading -- Japan -- History; Criticism -- Japan -- History; Japanese literature -- American influences; Electronic books